CONCEPTUAL MODEL FOR STRATEGIC ASSESSMENT OF INDUSTRIAL TRANSFORMATION IN ACCORDANCE WITH THE PRINCIPLES OF CARBON NEUTRALITY OF THE HYDROGEN ECONOMY - DMITRIIEVA, Oksana; KOTENOK, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In light of global challenges related to climate change and the necessity to reduce greenhouse gas emissions, the transformation of industry toward a carbon-neutral economy is becoming critically important. The aim of this study was to develop a conceptual model for the strategic assessment of industrial transformation in accordance with the principles of carbon neutrality, based on the implementation of a hydrogen economy.The results indicate that transforming industry in Ukraine toward a hydrogen-based carbon-neutral economy is key to reducing greenhouse gas emissions and achieving sustainable development. The main sources of emissions in Ukraine are the energy sector, industry, agriculture, and transport. Although emissions decreased from 2010 to 2023 — with a significant drop observed in 2022 — this may be due to economic changes or the implementation of new environmental standards.During this period, the share of renewable energy in Ukraine's energy balance increased from 4.8% in 2015 to 14.1% in 2023, indicating substantial progress in the transition to renewable energy sources. The reduction in the production cost of green hydrogen from UAH 2200/kg in 2015 to UAH 1400/kg in 2023 also makes it more competitive compared to traditional fossil fuels.The proposed conceptual model for strategic assessment of industrial transformation toward a carbon-neutral hydrogen economy encompasses two main levels: drivers of change and transformation strategies. The drivers of change include the circular economy, climate change, digitalization, and carbon neutrality. The transformation strategies focus on adapting industry to new conditions through innovative approaches, circular production, water conservation, and carbon neutrality.
Keywords: greenhouse gas emissions; sustainable development; renewable energy sources; green hydrogen; government policy; infrastructure